Financial Literacy, Social Status, Lifestyle, and FOMO on Generation Z Financial Management - Feby Pratiwi Handayani; Ardiansyah Japlani; Karnila Ali (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2025)
Purpose: This study examines the partial and simultaneous effects of financial literacy, social status, lifestyle, and Fear of Missing Out (FOMO) on personal financial management among Generation Z in Metro City, Lampung Province, Indonesia. Methodology: A quantitative descriptive survey was conducted with 100 Generation Z respondents (born 1997–2012) who had manageable income. Respondents were selected using purposive sampling methods. Data were collected using a validated and reliable Likert-scale questionnaire and analyzed using multiple linear regression after fulfilling classical assumption tests. Results: Financial literacy (β= 0.364, p< 0.001) and lifestyle (β= 0.201, p= 0.042) significantly and positively influenced personal financial management. Meanwhile, social status (β= 0.151, p= 0.067) and FOMO (β= 0.129, p= 0.142) have positive but statistically insignificant effects on purchase intention. Simultaneously, all variables significantly affected personal financial management (F= 19.471, p < 0.001), with an Adjusted R² of 0.823, indicating that 82.3% of the variance in financial management was explained by the model. Conclusions: Financial literacy is the most influential factor in shaping the financial management behavior of Generation Z, followed by lifestyle. Social status and FOMO did not independently exert significant effects. Limitations: This study is limited to Generation Z in Metro City and employs purposive sampling, which may reduce generalizability. Contribution: This study extends the understanding of Generation Z’s financial behavior by integrating financial literacy, social status, lifestyle, and FOMO, while emphasizing the importance of financial education in improving financial management practices.